Hypofractionated Stereotactic Radiotherapy after Transarterial Chemoembolisation Failure in an Unresectable Hepatocellular Carcinoma: A Case Presentation - Francesco Fiorica; Carlo Greco; Sergio Boccia; Sergio Sartori; Antonio Stefanelli; Francesco Cartei; Stefano Ursino (Case Reports in Hepatology)
Introduction. Transarterial chemoembolization is the first-line treatment in unresectable hepatocellular carcinoma. There is no standard treatment after transarterial chemoembolization failure. We report the case of a patient with advanced hepatocellular carcinoma who showed a complete response and a long cancer control with hypofractionated stereotactic radiotherapy after transarterial chemoembolization failure. Case Presentation. A 70-year-old Caucasian woman was treated with transarterial chemoembolization for advanced hepatocellular, but no cancer control was obtained. A hypofractionated stereotactic radiotherapy was planned delivering 40 Gy in 5 fractions. A dramatic reduction in alpha-fetoprotein was observed. Contrast-enhanced ultrasonography at 1 and 2 months showed large necrotic areas. Computerised tomography scan showed a 90% objective tumour response, then a complete remission at 3 and 6 months after treatment, respectively. Status of patient remained unchanged for 2 years. Conclusions. Hypofractionated stereotactic radiotherapy can improve survival and prognosis of unresectable hepatocellular carcinoma patient.